2012
DOI: 10.1182/blood-2011-12-396457
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 inhibits the viability, proliferation, and Th1 cytokine production of nonmalignant T cells in patients with leukemic cutaneous T-cell lymphoma

Abstract: Tumor-derived galectin-1 (Gal-1), a ␤-galactoside-binding S-type lectin, has been shown to encourage T-cell death and promote T cell-mediated tumor immune escape. In this report, we show that patients with leukemic cutaneous T-cell lymphomas, known to have limited complexity of their T-cell repertoires, have a predominant T helper type-2 (Th2) cytokine profile and significantly elevated plasma levels of Gal-1 compared with healthy controls. Circulating clonal malignant T cells were a major source of Gal-1. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 23 publications
2
66
0
4
Order By: Relevance
“…It is of note that many of the mutations we have detected in our mutational study affect signaling molecules such as CCR4, IL6S/T, and JAK proteins or those affecting the NFkB pathway that have been shown to regulate the acquisition of a Treg or a Th17 phenotype. 10 Interestingly, our data could provide a mechanistic explanation for the nature of the phenotypic plasticity that other researchers have seen in human CTCL samples [5][6][7]9 Although the exact contribution of these altered phenotypes to the pathogenesis of CTCL requires further attention, our mutational results strongly suggest that a number of genes and signaling pathways known to mechanistically control critical T-cell biological activities, including proliferation, survival, and differentiation, are recurrently targeted by somatic mutations in human MF/SS samples. This reveals potential targets for the development of new therapeutic strategies we can now begin to explore.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is of note that many of the mutations we have detected in our mutational study affect signaling molecules such as CCR4, IL6S/T, and JAK proteins or those affecting the NFkB pathway that have been shown to regulate the acquisition of a Treg or a Th17 phenotype. 10 Interestingly, our data could provide a mechanistic explanation for the nature of the phenotypic plasticity that other researchers have seen in human CTCL samples [5][6][7]9 Although the exact contribution of these altered phenotypes to the pathogenesis of CTCL requires further attention, our mutational results strongly suggest that a number of genes and signaling pathways known to mechanistically control critical T-cell biological activities, including proliferation, survival, and differentiation, are recurrently targeted by somatic mutations in human MF/SS samples. This reveals potential targets for the development of new therapeutic strategies we can now begin to explore.…”
Section: Discussionmentioning
confidence: 54%
“…Gene expression profiling studies have shown that increased signaling from the TCR can be considered a driving force of CTCL and that neoplastic T cells can show a degree of phenotypic plasticity, as characterized by the expression of a variety of lineage markers. [5][6][7][8][9] However, whether this is the result of signaling from the tumor stroma or the consequence of specific genetic alterations in the pathways involved in TCR signaling is still a matter of active research. [10][11][12] Early stages of CTCL are treated with combinations of UV and immunotherapy, with mono-or polychemotherapy being reserved for cases that do not respond to previous treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that in the keratinocytes from normal adult skin, Gal-1 was not evidenced. Remarkably, previous studies in human skin have shown that Gal-1 is not expressed by keratinocytes in normal skin [37] but can be expressed by cells in psoriasis [37,38], cutaneous malignant lesions including squamous cell carcinoma [39], mycosis fungoides [40,41], and melanoma [42], while in keloid tissues, proteome analysis of keloid proteins performed by Ong et al revealed that the expression of Gal-1 is upregulated compared to normal skin [43]. However, the role of Gal-1 in skin lesions is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-1, like others galectins, participates in signaling pathways and regulates a variety of biological responses including cell growth, cell-cell and cell-matrix adhesion, cell differentiation, migration, proliferation and survival [31][32][33][34] and plays a critical role in inflammation, angiogenesis, and tumor development and progression [27,33,35,36]. In human skin, Gal-1 has been implicated in psoriasis [37,38] and malignant lesions including cutaneous cancer [39], mycosis fungoides [40,41], and melanoma [42], and scarce studies have shown that the expression of Gal-1 is upregulated in keloid tissue [43]. However, the presence, distribution, and localization of Gal-1 as well as its possible role in benign dermal fibroproliferative tumors such as keloids, have not been completely elucidated.…”
mentioning
confidence: 99%
“…Targeting GAL1 in carcinoma-associated fibroblasts inhibits oral squamous cell carcinoma metastasis by downregulating MCP-1/CCL2 expression (18). However, some reports show GAL1 inhibits the viability, proliferation and Th1 cytokine production of non-malignant T cells in patients with leukemic cutaneous T-cell lymphoma (19), and GAL1 silencing imparts colorectal cancer with the ability to proliferate and escape apoptosis (20). Further research suggests that GAL1 plays vital pro-tumorigenic roles within the tumor microenvironment (21), and stimulates the proliferation of melanoma and neo-angiogenesis processes (22).…”
Section: Discussionmentioning
confidence: 99%